Analyis Penataan Fasilitas dan Lanskap Sesuai dengan Permenparekraf No 4 Tahun 2021 di Teras Sejiwa Café - Yanti, Dewi (Politeknik Pariwisata Medan, 2024)
Landscape is stated as a land that has certain forming elements, composition and characteristics as its differentiator. (Dina et al., 2005) According to Eckbo in his book entitled